Reliability of cycling gross efficiency using the Douglas bag method - Hopker, J. G.; Jobson, S. A.; Gregson, H. C.; Coleman, D.; Passfield, L. (Medicine & Science in Sports & Exercise, 2012)
Purpose: The aim of this study was to establish the reliability of gross efficiency (GE) measurement (the ratio of mechanical power input to metabolic power output, expressed as a percentage) using the Douglas bag method.